Labor Market Returns to Education and English Language Skills in the People's Republic of China: An Update - Niaz Asadullah; Saizi Xiao (Institute of Labor Economics (IZA), 2018)
We re-examine the economic returns to education in the People's Republic of China (PRC) using data from the China General Social Survey 2010. We find that the conventional ordinary least squares estimate of returns to schooling is 7.8%, while the instrumental variable estimate is 20.9%. The gains from schooling rise sharply with higher levels of education. The estimated returns are 12.2% in urban provinces and 10.7% in coastal provinces, higher than in rural and inland areas. In addition, the wage premium for workers with good English skills (speaking and listening) is 30%. These results are robust to controls for height, body weight, and English language skills, and to corrections for sample-selection bias. Our findings, together with a critical review of existing studies, confirm the growing significance of human capital as a determinant of labor market performance in post-reform PRC.
Keywords: I26; J30; 330; endogeneity bias; language skills; schooling; health